Environmental factors affecting the formation and occurrence of natural hazards rural settlements Silakhor Plains in Lorestan Province - Dariush Yarahmadi; Siyamack Sharafi (مخاطرات محیط طبیعی, 2016)
In principle, the appearance of a village more than anything is dependent upon the environmental conditions and geographical position. Thus identifying the environmental factors which influence the formation of rural habitats is highly important. The Silakhor plain in the northeast of Lorestan Province is an area with its favorable environmental factors for inhabitation, and a dense drainage network of major and minor faults. But it has a variety of natural hazards. In this paper, descriptive – analytical and statistical research methods have been used along with tools like topography, geology, and geomorphology maps, water resources and satellite imagery. To overlay the layers, Arc GIS software tools and AHP methods were used. Results indicate that the most important geomorphic factors in the dispersal establishment of villages are alluvial plains. The most stable Ecological factors which affect the distribution of villages in the Silakhor plain is the slope factor and the most instable ones are several faults that cause earthquakes in the region. From the natural hazards viewpoint, the results show that in the Silakhor plain from among 223 villages, 18 villages are at the risk of flooding, 41 villages at the risk of landslides, and 66 villages are located in high earthquake risk regions. Finally, the compilation hazard maps show that 18 villages are highly vulnerable to natural disasters.